Potential Antioxidant Activity Of Coconut Kentos Flour (Cocos nucifera L.) And Application In Biscuits - Liza Kolondam; Gregoria S. S. Djarkasi; Jein R. Leke; Christine F. Mamuaja; Jantje Pongoh (Jurnal Agroekoteknologi Terapan, 2023)
Kentos is the fruit of a coconut seed that germinates or sprouts as a result of a biochemical process. This research will look at the potential antioxidant activity of coconut kentos flour (Cocos nucifera, L) and its application to biscuits. This study aims to determine the bioactive components of kentos, to determine the antioxidant activity of kentos flour biscuits and to determine the level of preference of panelists for kentos flour biscuits. The research method for the organoleptic test was a completely randomized design (CRD) with 5 treatments and 3 replications. The results obtained were that the best antioxidant activity was found at 30 days of age 31.21%, 56.95%, 77.22%, 89.94% and 92.90% with an IC50 of 3.6 mg/g. The highest total phenol analysis was found at the age of 15 days 0.092 mg GAE/g. The P4 treatment was the best result received by the panelists in organoleptic testing with an average color, aroma, taste and texture test, namely 132, 132.66, 132.33 and 131.66. Kentos flour biscuit antioxidant activity aged 30 days was 91.30%, 91.04%, 90.92%, 90.81% and 90.54% with IC50 236.31%. Total phenol of kentos flour biscuits was 0.045 mg GAE/g. Keywords: Kentos, Coconut Germination, Antioxidant Activity, Organoleptic Test Abstrak Kentos adalah buah dari biji kelapa yang berkecambah atau bertunas akibat proses biokimia. Penelitian ini akan melihat potensi aktivitas antioksidan tepung kentos kelapa (Cocos nucifera, L) dan aplikasinya pada biskuit. Penelitian ini bertujuan untuk mengetahui komponen bioaktif pada kentos, mengetahui aktivitas antioksidan pada biskuit tepung kentos dan mengetahui tingkat kesukaan panelis terhadap biskuit tepung kentos. Metode penelitian pada uji organoleptik yaitu Rancangan Acak Lengkap (RAL) dengan 5 perlakuan dan 3 kali ulangan. Hasil yang diperoleh adalah aktivitas antioksidan terbaik terdapat pada umur 30 hari 31,21%, 56,95%, 77,22%, 89,94% dan 92,90% dengan IC50 3,6 mg/g. Analisis total fenol tertinggi terdapat pada umur 15 hari 0,092 mg GAE/g. Perlakuan P4 merupakan hasil terbaik yang diterima oleh panelis pada pengujian organoleptik dengan rata-rata pada pengujian warna, aroma, rasa dan tekstur yaitu 132, 132,66, 132,33 dan 131,66. Aktivitas antioksidan biskuit tepung kentos umur 30 hari 91,30%, 91,04%, 90,92%, 90,81% dan 90,54% dengan IC50 236,31%. Total fenol biskuit tepung kentos 0,045 mg GAE/g. Kata Kunci: Kentos, Germinasi Kelapa, Aktivitas Antioksidan, Uji Organoleptik